DATA MINING ON PHOSPHATASES FROM THE REFERENCE GENOM OF RAHNELLA AQUATILIS BACTERIA: https://doi.org/10.5281/zenodo.15352334 - Yakubov I.Т; Shovazova , Z.K; Saydalieva , Sh.S; Shakirov, Z.S (International scientific and practical conference, 2025)
Due to the annual population growth in our country, it is necessary to obtain high-quality plant production yields and enhance soil fertility to ensure the population is supplied with food and agricultural products. One of the key conditions for increasing agricultural productivity is the level of phosphorus availability to plants. Phosphorus, along with nitrogen, is an essential nutrient for plants. It is involved in almost all major metabolic processes in plants, including nucleic acid synthesis, photosynthesis and respiration, energy metabolism and storage, molecular biosynthesis and signal transduction, as well as nitrogen fixation in legumes.